To the spectral theory of the Bessel operator on finite interval and half-line - Ananieva, A.Yu.; Budyika, V.S. (Український математичний вісник, 2015)
The minimal and maximal operators generated by the Bessel differential expression on the finite interval and a half-line are studied. All non-negative self-adjoint extensions of the minimal operator are described. Also we obtain a description of the domain of the Friedrichs extension of the minimal operator in the framework of extension theory of symmetric operators by applying the technique of boundary triplets and the corresponding Weyl functions, and by using the quadratic form method.